The Dynamics of Islamic Family Law Reform in Morocco on Guardians Of Marriage - Nur Aini Awaliyah (Indonesian Journal of Law and Islamic Law (IJLIL), 2022)
Islamic law reform must be carried out in response to the demands of change that occur in society. It is said that because one form of the universality of Islamic law is seen from the adaptability and flexibility of Islamic law itself. In connection with reform, Morocco carried out reforms of Islamic family law in the twentieth century. History states that between 1912-1956 Morocco was under French and Spanish political domination. The follow-up of efforts to develop the codification of family law was on August 19 1957, Morocco, whose inhabitants were followers of the Maliki school of thought, codifying during 1957 to 1958 producing Mudawwamah al-Ahwal al-Syakhsiyyah. The history of the birth of the Moroccan Law began on December 6, 1957 (13 Jumadil Awal 1377) with the issuance of the King's decree dated November 22, 1957 (28 Rabiul Thani 1377), announcing the issuance of the law on marriage and divorce. Morocco made history again in 2004, Morocco carried out a reform of the Islamic family law, which is one of the countries that gives legal permission to a woman, both girl and widow, to marry herself without a guardian in its Mudawwah al-Usrah, efforts to reform this law cannot be separated from the role of King Muhammad VI and the Progressive Feminism Movement.